Linguistic and sociolinguistic aspects of the omission of sounds and syllables in isiXhosa speech: an explanatory guide for 2nd language learners of the language - Mahlumba, Esethu (School of Languages and Literatures, 2025)
The shortening of words, sometimes even to just one syllable, variously referred to as clipping, reduction and truncation, is a recognized phenomenon in slang but also in authentic speech. Most of us know that the English farewell “Goodbye!” often reduced to just “Bye!” is a clipped form of “God be with you” and that “ad” is a shortened form of “advertisement”. In fact, a body of scholarship on historical and contemporary clippings in English and many of the world's languages has, and continues to be, developed. The reduction of sounds in the lexicons of African languages, particularly Xhosa, is, however, a neglected field – a lacuna that I noticed when struggling to explain the phenomenon to English and Afrikaans speakers who could not align the written Xhosa word with its spoken form. In this thesis, therefore, I foreground the struggles of 2nd language learners of Xhosa at the University of Cape Town in comprehending spoken Xhosa and explain that being a tutor of the language at this level led me to conduct the research. I felt the need to establish a data-base of the most commonly truncated forms in the language and the phonological processes at play so that entry level students of the language (as a 2nd language) as well as more advanced learners would have access to commonly reduced words as well as explanations of the most widely occurring phonological processes involved in the omission of sounds. To ensure that the research kept its focus on actual student needs, a short survey was conducted with 2nd language students of Xhosa at the university to ascertain the extent to which they see the development of listening skills as desirable in a communication course. In addition, a pilot listening test was conducted with two groups of students – the one group receiving an intervention providing information on reduced forms in Xhosa, the other group taking the test without the intervention. Scores are tabulated and discussed and recommendations made based on the outcomes of both the survey and the tests.